The Role of Virtuous Leadership In Reducing Organizational Deviation: An Analytical Study of A Sample of Al-Rafidin In Bank Employees in Anbar - Fouad Zabar, Hind; Rashid Musehib, Mohsen (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research works to achieve several goals, perhaps the most prominent of which is identifying the role of virtuous leadership in reducing organizational deviation. Theoretical Framework: Based on what the researchers reported (G. Wang & Hackett, 2016), (Bashir et al., 2012) this study deals with providing practical guidance to improve the virtuous leadership process and enhance its effectiveness in reducing deviations and achieving sustainable development. Design/Methodology/Approach: The study analyzed the data of Rafidain Bank employees in Anbar (2023-2024) using the virtuous leadership model and through its dimensions (courage, wisdom, justice, moderation, and humanity) in reducing organizational deviation through the dimensions (waste of time and resources, sabotage, embezzlement, withdrawal, and corruption). Findings: The most notable results are that there is an influential relationship between virtuous leadership and organizational deviation Research Implications: The results confirm the presence of some cases of embezzlement among bank employees due to their use of office tools for their own purposes, and their taking of things belonging to others while working surreptitiously and without approval. Originality/Value: This study works to identify and develop the qualities and skills necessary for virtuous leaders, which leads to the improvement and development of banking work.